O surgimento do PC do B na crise do comunismo brasileiro entre 1954 a 1962 - Carvalho, Daniel Ilirian (2010)
This Master's degree dissertation is about the division of PCB occurred in the early 1960 s, when the PCdoB has created as a counterpoint of that previous organization. To conduct this research, official documents of the PCB had been used. They consisted in Theses for Discussion and articles produced by the Communist leadership and published on Communist newspaper Novos Rumos (New Paths) during the V Congress held in 1960; the Declaration of March produced and published by the PCB in 1958 and the Manifesto Program produced and published by the dissidents who have created the PCdoB in February 1962. To deals with these documents, it was extract their most recurrent themes, not giving previous defined meanings to the information , but taking in account the logic that led those debates in that moment, understanding more precisely the historical context. The objective of this research was to analyze the differences and circumstances that led to the split of the Communist Party, considering the proposals contained in the debate between its leadership. These debates were related mainly to the understanding about the nationalist-development politics that was a part of the a Juscelino Kubitschek s administration, as well as the relations between Brazil and the imperialist countries and the contradictions caused by the Brazilian capitalism, from which it was surged the Party s political strategy on social relationship between the working class and the bourgeoisie, and the proposed Frente Única (Unique Front). It was observed that the difficulties to understanding the political processes and their connections with national development, as well as the controversy about the consequences of deepening the relations to the foreign capital, have led to the split of Communists at that moment, beside the suspicion about the Brazilian bourgeoisie real wishes, which even divided, simply wanted to recover its positions at the Juscelino s government, without changing social structures